2007
DOI: 10.1111/j.1365-2362.2007.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated Vegfr2/kdr Pathway In Tumour Cells And Tumour Associated Vessels Of Colorectal Cancer

Abstract: pVEGFR2 receptors are largely expressed in colon cancer cells and intratumoural vasculature. As VEGF targeting agents enter the clinical practice, the role of monoclonal antibodies recognising the phosphorylated form of VEGF receptors as predictors of response to targeted therapies should be sought in clinicopathological trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 37 publications
0
63
0
1
Order By: Relevance
“…IGF-1R, which is expressed at low levels in normal hepatocytes, is also overexpressed in human HCC tissues, whereas the expression levels of IGFBP-3, a negative regulator of the IGF/IGF-1R axis, are decreased in human HCC samples and this is associated with poor survival of HCC patients [31][32][33]. In addition, an overexpression and activation of the VEGF/VEGFR axis is observed in both human CRC and HCC, and this has also been shown to correlate with poor prognosis for these malignancies [34][35][36][37]. Therefore, targeting these RTKs and their downstream pathways may be a potentially effective strategy for the prevention and, in certain cases, treatment of some types of human malignancies, including CRC and HCC [9][10][11].…”
Section: Abnormalities In Rtks and Colorectal And Liver Cancersmentioning
confidence: 99%
“…IGF-1R, which is expressed at low levels in normal hepatocytes, is also overexpressed in human HCC tissues, whereas the expression levels of IGFBP-3, a negative regulator of the IGF/IGF-1R axis, are decreased in human HCC samples and this is associated with poor survival of HCC patients [31][32][33]. In addition, an overexpression and activation of the VEGF/VEGFR axis is observed in both human CRC and HCC, and this has also been shown to correlate with poor prognosis for these malignancies [34][35][36][37]. Therefore, targeting these RTKs and their downstream pathways may be a potentially effective strategy for the prevention and, in certain cases, treatment of some types of human malignancies, including CRC and HCC [9][10][11].…”
Section: Abnormalities In Rtks and Colorectal And Liver Cancersmentioning
confidence: 99%
“…Importantly, Guo et al found that KDR could regulate tumor angiogenesis directly [29]. It is reported that overexpression of KDR had close-knit association with many kinds of cancers, such as lung cancer, breast cancer, ovarian cancer, colon cancer, and uterus cancer [29][30][31]. Subsequently, Knizetova et al found that KDR played the role as intracellular regulator mainly via some important signaling cascades, such as the pathways of PLC/ PKC, c-Raf/MAPK, and P13 K/Akt [32].…”
Section: Introductionmentioning
confidence: 97%
“…in the literature, we found no studies measuring VeGFr-1 or VeGFr-2 protein concentrations in crc and normal colorectal tissue using the quantitative eliSa technique. a few studies using semi-quantitative techniques, such as immunohistochemistry, found indications of higher VeGFr-2 protein expression in crc compared to normal colorectal tissue (18,19), but a direct comparison with our study is of course not possible due to the substantial differences in the techniques employed.…”
Section: Discussionmentioning
confidence: 39%